Liv i rörelse Göteborgs befolkning och arbetsmarknad 1900-1950 - Karlsson, Tobias; Lundh, Christer (Kriterium, 2022)
During the first half of the twentieth century, the industrialization of Sweden was completed. A substantial proportion of the population resided in cities. What did the life courses of these people actually look like? In this book, four researchers have studied a random sample of men and women in Gothenburg, tracing their movements through the various phases of life, and between residences, working places and occupations. It is an account of important events in the lives of ordinary people during a period when much of the modern society was formed.